AI, Big Data, and IoT for Social and Environmental Sustainability in a Digital Transformation Course - Opromolla, Antonio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
Social sciences increasingly focus on the intricate interplay between social organizations and technological systems, termed socio-technical systems. This concept highlights how these interactions influence societal structures and functions, necessitating strategies to drive positive social impact by integrating social, economic, and environmental sustainability. For example, fostering participation and inclusion can centralize environmental issues and promote sustainable production. Managing these complex processes requires new skills. Design sociology offers a solution by applying design tools and concepts to research, generating insights for societal solutions. Design thinking, a human-centered approach, aims to induce cultural changes and develop new forms. This paper underscores the need for these skills in educational curricula. It details a training module on digital transformation, applying human-centered design to create interactive solutions with societal and environmental benefits. Students select a Sustainable Development Goal and use AI, Big Data, and IoT in an iterative process to achieve their targets. The paper outlines the module's steps, objectives, materials, and outcomes from higher education student applications.